Human traffic monitoring using radar technology - Teo, Yi Xian (Nanyang Technological University, 2022)
In recent years, crowd monitoring technology has had significant advancements with a variety of purposes. However, different technologies used to perform crowd monitoring can lead to different effects and limitations, therefore more investigative work on the different types of technology is required. The aim of the project is to develop a prototype that uses a radar sensor to collect data for human traffic monitoring, where the density and movement of crowds in public places will be measured with the capabilities of the radar sensor.